Being friendly to the skin microbiome: Experimental assessment - van Belkum, Alex; Lisotto, Paola; Pirovano, Walter; Mongiat, Sebastien; Zorgani, Amine; Gempeler, Mathias; Bongoni, Radhika; Klaassens, Eline (Frontiers in Microbiomes, 2023)
Both academia and dermatological and cosmetic industries have acknowledged that healthy skin microbiota contribute to overall skin integrity and well-being. This implies that formulations developed for personal care (skin, scalp, hair etc) or (medical and cosmetic) treatment need to be compatible with microbiota conservation or possibly even improvement. Consequently, the various chemical and biological components and mixtures thereof intended for direct application to the skin should not extensively affect the qualitative and quantitative composition of the skin microbiota. Preferably, a compound should promote beneficial microbes and inhibit pathogens. As such, compounds but also final products could be considered at least theoretically “microbiome friendly” while in some cases changes to the microbiota may even be considered beneficial. An important hurdle lies in the practical and methodological approaches to be used for defining microbiota inertia of compounds and formulations. Currently, clear guidelines for assessing microbiome friendliness are lacking. We here propose three associated testing concepts that may help to define microbiome friendliness based on the assessment of minimal microbiota perturbation and even elimination of potential pathogens. Methods to prove microbiome friendliness should ultimately be based upon next generation sequencing of naive versus compound- or final product-exposed skin microbiota in vivo, but preferably also including in vitro and ex vivo pre-screening methodologies to build an understanding of their mechanism of action. As in many domains of microbiome research, the development of experimental process controls and internal standards, which are essentially lacking to date, should be taken as a future prerequisite. There is also a requirement from regulatory agencies to define and harmonize acceptance criteria.